2011
DOI: 10.1080/13588265.2011.554203
|View full text |Cite
|
Sign up to set email alerts
|

A multi-body systems approach to simulate helicopter occupant protection systems

Abstract: This paper reports on the work of computer simulations carried out at Coventry University as part of the European 6th Framework HeliSafe TA project, which considered the potential improvements in occupant safety for civil helicopters. A multi-body systems approach with additional use of finite elements for critical components such as a pilot airbag and the harnesses was adopted in the computer models to simulate helicopter crash/rollover scenarios and to investigate the effectiveness of occupant protection sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Studies using crash test dummies have found that airbag restraints provide greater protection than standard restraints (Wright and Albery 2013 ). Airbags decrease pilot forward motion (Vadlamudi et al 2011 ) and can prevent impact with objects or the helicopter structure, reduce slack in restraints, and reduce head movement (Bolukbasi et al 2011 ; DOD 2009 ; Ford 1995 ). Cockpit airbag systems and belt retractors that position occupants appropriately prior to impact can reduce flailing (Bolukbasi et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using crash test dummies have found that airbag restraints provide greater protection than standard restraints (Wright and Albery 2013 ). Airbags decrease pilot forward motion (Vadlamudi et al 2011 ) and can prevent impact with objects or the helicopter structure, reduce slack in restraints, and reduce head movement (Bolukbasi et al 2011 ; DOD 2009 ; Ford 1995 ). Cockpit airbag systems and belt retractors that position occupants appropriately prior to impact can reduce flailing (Bolukbasi et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using crash test dummies have found that airbag restraints provide greater protection than standard restraints (Wright and Albery 2013). Airbags decrease pilot forward motion (Vadlamudi et al 2011) and can prevent impact with objects or the helicopter structure, reduce slack in restraints, and reduce head movement (Bolukbasi et al 2011;DOD 2009;Ford 1995). Cockpit airbag systems and belt retractors that position occupants appropriately prior to impact can reduce ailing (Bolukbasi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using crash test dummies have found that airbag restraints provide greater protection than standard restraints (Wright and Albery 2013). Airbags decrease pilot forward motion (Vadlamudi et al 2011) and can prevent impact with objects or the helicopter structure, reduce slack in restraints, and reduce head movement (Bolukbasi et al 2011;DOD 2009;Ford 1995). Cockpit airbag systems and belt retractors that position occupants appropriately prior to impact can reduce ailing (Bolukbasi et al 2011).…”
Section: Discussionmentioning
confidence: 99%